Training and Mentoring in Making Seuke Mats Using Decorative Techniques to Improve the Economy of Home Industries (IRT): Pelatihan dan Pendampingan Pembuatan Tikar Seuke Dengan Teknik Dekoratif Meningkatkan Perekonomian Industri Rumah Tangga (IRT) - Uci Dwi Cahya; Fauziansyah; Hendra Susanto (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2026)
The creative industry training program, which focuses on handicrafts made from woven pandan leaves, is an effort to empower the community of Seuneubok Village, Pidie, East Aceh Regency, to improve their economy and skills. Through the training and mentoring, participants are equipped with skills ranging from material preparation to decorative techniques for creating innovative products such as mats, prayer rugs, bags, and more. Furthermore, participants are taught digital marketing strategies to expand their market reach using the Google My Business application. The training results indicate an increase in community skills, with 90% of participants mastering basic techniques in a short time. This program not only supports economic independence but also strengthens awareness of sustainable local resource management. The implementation of this training serves as a model for sustainable community empowerment based on local wisdom, providing significant social and economic impacts for the community of Seuneubok Village, Pidie, East Aceh Regency.